"Not being able to talk was horrid": A descriptive, correlational study of communication during mechanical ventilation. Issue 3 (June 2015) - Guttormson, Jill L.; Bremer, Karin Lindstrom; Jones, Rachel M.
Summary Objectives The purpose of this study was to describe the patient experience of communication during mechanical ventilation. Research methodology: This descriptive study is a secondary analysis of data collected to study the relationship between sedation and the MV patients' recall of the ICU. Interviews, conducted after extubation, included the Intensive Care Experience Questionnaire. Data were analysed with Spearman correlation coefficients (rs) and content analysis. Setting Participants were recruited from a medical-surgical intensive care unit in the Midwest United States. Results Participants (n = 31) with a mean age of 65 ± 11.9 were on the ventilator a median of 5 days. Inability to communicate needs was associated with helplessness (rs = .43). While perceived lack of information received was associated with not feeling in control (rs = 41) and helplessness (rs = 41). Ineffective communication impacted negatively on satisfaction with care. Participants expressed frustration with failed communication and a lack of information received. They believed receipt of information helped them cope and desired a better system of communication during mechanical ventilation. Conclusion Communication effectiveness impacts patients' sense of safety and well-being during mechanical ventilation. Greater emphasis needs to be placed on the development and integration of communication strategies into critical care nursing practice.